2019
DOI: 10.1136/bmjopen-2018-024920
|View full text |Cite
|
Sign up to set email alerts
|

Long-term observational approach in women with histological diagnosis of cervical low-grade squamous intraepithelial lesion: an Italian multicentric retrospective cohort study

Abstract: ObjectiveTo evaluate the risk of progression to high-grade squamous intraepithelial lesion (HSIL) (CIN2-3) or invasive cancer in women with histopathological diagnosis of low-grade squamous intraepithelial lesion (LSIL) (CIN1), managed in a long-term observational approach up to 5 years.DesignRetrospective cohort study.SettingFour tertiary referral hospital.Participants434 women with adequate colposcopy and complete colposcopic charts were included in the present analysis. Women with glandular lesions on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…We showed that the switch to the hrHPV‐based screening programme leads to an increase in the detection rates of low‐grade CIN lesions. Most of the detected low‐grade lesions will not progress 7 . Previous studies on triage strategies have shown that the number of unnecessary referrals to colposcopy could be reduced by the use of genotyping 33 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We showed that the switch to the hrHPV‐based screening programme leads to an increase in the detection rates of low‐grade CIN lesions. Most of the detected low‐grade lesions will not progress 7 . Previous studies on triage strategies have shown that the number of unnecessary referrals to colposcopy could be reduced by the use of genotyping 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the detected low-grade lesions will not progress. 7 Previous studies on triage strategies have shown that the number of unnecessary referrals to colposcopy could be reduced by the use of genotyping. 33 Genotyping is not used in the current Dutch hrHPV-based screening programme but should be considered to reduce the number of colposcopies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 However, there is still a part of LSIL that progresses to HSIL. 30 The diagnostic accuracy of traditional colposcopy in detecting HSIL or worse (HSIL+) ranged only from 30 to 70%. 31 The sensitivity of colposcopy diagnosis for high‐grade lesions/carcinoma (HSIL+) was 71.6% in a study from Tianjin, China 8 and 80.9% in a recent study from Chengdu, China.…”
Section: Discussionmentioning
confidence: 99%
“…The first, well described and accepted pathway suggests that HSIL develops via LSIL and that LSIL originates in the ectocervical epithelium by high risk human papilloma virus (hrHPV) infection of the basal cell compartment in the squamous epithelium. 24,41,47,48 A second theory states that HSIL is the result of a hrHPV infection of IMM, as concluded from the dual expression of keratin 17 and p16 in atypical squamous lesions with metaplastic features. 6,13,22,43,45 The third pathway involves hrHPV infection of the specific stretch of endocervical, keratin 7-positive cuboidal cells at the SqCJ, producing immediately a HSIL without a low-grade precursor lesion.…”
Section: Discussionmentioning
confidence: 99%